Surgical treatment of nonobstructive azoospermy, caused by hypergonadotropic hypogonadism - О. D. Nikitin (Клінічна хірургія)
Objective. Determination of efficacy of intracytoplasmatic introduction of spermatozoid (ICSI) in treatment of infertile men, suffering hypergonadotropic hypogonadism, complicated by nonobstructive azoospermia (NОА), using technologies of TESE (еxtraction of spermatozoids), TESA (transcutaneous аspiration of sperm from testicle), аnd their combination (TESE and TESA) as well for the sperm cells extraction.